2023
DOI: 10.1101/2023.02.09.527813
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Direct observation of a crescent-shape chromosome inBacillus subtilis

Abstract: Bacterial chromosomes are folded into tightly regulated threedimensional structures to ensure proper transcription, replication, and segregation of the genomic information. Direct visualization of the chromosomal shape within bacterial cells is hampered by cell wall confinement and the optical diffraction limit. Here, we combine cell-shape manipulation strategies, high resolution fluorescence microscopy techniques, and genetic engineering to visualize the intrinsic shape of the bacterial chromosome in real tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 84 publications
0
1
0
Order By: Relevance
“…Interestingly, previous work showed that brief rifampicin treatment of bacterial cells showed a complete loss of any higher-order organization within the origin region [64][65][66] , which is surprising as ParB proteins should have been unaffected in their ability to locally condense the DNA in the partition complex. This observation is consistent with the hypothesis that supercoiling is a crucial facilitator for the maintenance of the ParB-DNA partition complex, especially considering the small number of ParB proteins (~250-700) in a bacterial cell 23,25 .…”
Section: The Impact Of Parb On Supercoiled Dnamentioning
confidence: 96%
“…Interestingly, previous work showed that brief rifampicin treatment of bacterial cells showed a complete loss of any higher-order organization within the origin region [64][65][66] , which is surprising as ParB proteins should have been unaffected in their ability to locally condense the DNA in the partition complex. This observation is consistent with the hypothesis that supercoiling is a crucial facilitator for the maintenance of the ParB-DNA partition complex, especially considering the small number of ParB proteins (~250-700) in a bacterial cell 23,25 .…”
Section: The Impact Of Parb On Supercoiled Dnamentioning
confidence: 96%